Assessing soil and native high Andean grassland quality under grazing: A case study from the wet Puna of Peru - Arias Arredondo, Alberto Gilmer (2026)
High Andean grasslands are vulnerable to changes in their nutritional quality and carbon sequestration capacity, especially in grazing systems. This study evaluated soil quality and native grasses by measuring carbon, physicochemical parameters, and the nutritional quality of predominant species in the wet Puna of Junín, Peru. Significant differences were found in carbon storage and nutritional quality across different grazing grassland sites. Soil carbon levels were consistently high across all sites, with significant concentrations at San Pedro de Cajas (14.26% ± 11.7%; p < 0.05), and its carbon stock (210.7 ± 111.3 Mg/ha) exceeded that of Junín (+68%) and Ulcumayo (+107%). Also, the flat topography at this site is presumed to have influenced its soil fertility. No adverse relationship was observed between carbon content and animal units, regardless of continuous or rotational grazing system, and a strong negative Pearson correlation (r = 0.84) between total carbon and bulk density indicated the prevalence of organic materials and no soil compaction. It emphasizes how landscape features affect soil quality and ecosystem processes. The protein content of key species exhibited a strong Pearson correlation with plant phosphorus (r = 0.93), digestible organic matter (DOM), and metabolizable energy (ME; r = 0.75). The Redundancy Analysis (RDA) showed that plant functional traits are driven by chemical and physical gradients, underscoring the combined effects of nutrient availability and site constraints on pasture productivity and forage quality. Among native grasses, Cebadilla (Calamagrostis vicunarum [Wedd.] Pilg.) emerged as the most favorable option for animal nutrition and exhibited a significantly higher crude protein content (8.23% ± 0.89%), Metabolizable energy value (8.16 MJ/kg), and C/N ratio (~40). Future research should focus on linking soil and forage quality with animal physiological responses to improve understanding of grazing impacts and guide sustainable management in high-altitude grasslands.